Effects of Beverage Can Body Addition on β Phase Modification in Recycled Al-Si-Fe Cast Alloy - Luijan, Jinkamon; Muangnoy, Phisit (Journal of Advanced Development in Engineering and Science, 2023)
The objective of this research was to study the effects of beverage can body addition on the phase modification in recycled Al-Si-Fe cast alloys. Beverage can body parts with different proportions (5, 10, 20 and 30 wt.%) were added into the molted Al-Si-Fe alloy for 30 minutes holding time, then poured into a stainless steel mold at 0.2 °C/s cooling rate. The result on the beverage can body microstructure was found to consist of Al6(Mn,Fe) and Mg2Si phases. The microstructure of the Al-Si-Fe cast alloy indicates that the phase that distributes in the -Al matrix. After the addition of 5 wt.% of the beverage can body, the size and length of the phase decreases. The addition of 10, 20 and 30 wt.% of beverage can body showed transformation from the phase to the phase. In particular, the addition of 30 wt.% of the beverage can body which led to the most efficient of modification of the phase. The quantitative analysis of the phases showed that the phase decreased by 50-80 % depending on amount the beverage can body addition.